1981
DOI: 10.1159/000117856
|View full text |Cite
|
Sign up to set email alerts
|

Cell Membrane Predictors of Response to Lithium Prophylaxis of Affective Disorders

Abstract: HLA antigens and RBC/plasma lithium ratio were studied in a sample of 49 patients, diagnosed as bipolar affective psychotics (n = 22), unipolar depressive psychotics (n = 18) and cycloid psychotics (n = 9), receiving prophylactic lithium for 1–4 years and maintained at lithium plasma levels of 0.6–1.2 mEq/1. Mean values of the ratio were found to be significantly higher in patients who responded to treatment when compared with non-responders, whereas the frequency of the HLA-A3 antigen was significantly higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…3) platelet MA0 activity (by a radioenzymatic method, using tryptamine and beta-phenylethylamine as substrates (21), testing each patient while euthymic, at least twice during the follow-up period), and 4) HLA antigens (by the standard NIH microcytotoxicity test (9). Statistical significance of differences between responders and non-responders was evaluated by the Student's t test and the x 2 method with Yates' correction.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…3) platelet MA0 activity (by a radioenzymatic method, using tryptamine and beta-phenylethylamine as substrates (21), testing each patient while euthymic, at least twice during the follow-up period), and 4) HLA antigens (by the standard NIH microcytotoxicity test (9). Statistical significance of differences between responders and non-responders was evaluated by the Student's t test and the x 2 method with Yates' correction.…”
Section: Methodsmentioning
confidence: 99%
“…the occurrence of more than three affective episodes within 1 year), a history of alcoholism or drug abuse not associated with mood changes, and the presence of paranoid features in the clinical picture have been cited as clinical predictors of a poor response (3,4). Among biological variables, high values of the red blood celVplasma lithium ratio (5,6) and a significantly elevated potential difference across the rectal mucosa (7) have been found to be associated with a favourable response to prophylaxis, while the presence of the HLA-A3 antigen has been reported to be significantly more frequent in non-responsive patients (8,9). Finally, evidence has been claimed of higher mean scores on the Obsessional Scale of the Middlesex Hospital Questionnaire in lithium-responsive patients (10) and on the Neuroticism Scale of the Eysenck Personality Questionnaire in non-responders (1 1).…”
mentioning
confidence: 99%
“…found that the frequency of HLA‐A3 antigen was significantly higher in lithium non‐responders 59 . This relationship between HLA‐A3 antigen and non‐response to prophylactic treatment by lithium was confirmed by other researchers 7,60 , 61 . However, subsequent studies could not replicate an association between affective disorder and HLA antigens 62–65 .…”
Section: Human Leukocyte Antigen Typingmentioning
confidence: 69%
“…59 This relationship between HLA-A3 antigen and non-response to prophylactic treatment by lithium was confirmed by other researchers. 7,60,61 However, subsequent studies could not replicate an association between affective disorder and HLA antigens. [62][63][64][65] This questioned the possible relationship between lithium response and HLA.…”
Section: Human Leukocyte Antigen Typingmentioning
confidence: 99%
“…Differences in cellular HLA surface protein composition between BPD patients who respond well to lithium and non-responders were first reported over 30 years ago in several studies. These reports noted that leukocyte HLA-A3 antigen reactivity was reported to be associated with poor lithium response, whereas the absence of HLA-A3 predicted a favorable response [58][59][60] . At the same time, in vitro experiments suggested that lithium binds to HLA antigens on cultured human leukocytes 61 .…”
Section: Discussionmentioning
confidence: 99%